A rapid method for constructing precaution maps based on a simple virtual ecology model: a case study on the range expansion of the invasive aquatic species Limnoperna fortunei. Issue 3 (4th June 2015) - Osawa, Takeshi; Ito, Kenji
Abstract: Before invasion, or in its early stages, information on the invader in target areas is generally extremely limited. In such situations, managers must select focal areas in which to concentrate control and mitigation efforts. Here, we discuss a rapid method for selecting areas in which to control invasive aquatic species based on limited information. We used a simple cellular automata model that does not require species‐specific information, but simulates the process of invasive species expansion and includes observed expansion progress to detect keystone areas. As a case study, we simulated the expansion of an invasive aquatic mussel, Limnoperna fortunei, in Ibaraki Prefecture, Japan, and detected the areas in which control efforts should be concentrated. To some extent, our model was able to predict the expansion of L. fortunei from the initial detected invasion to the current distribution. We predicted areas with a high potential of spreading and areas that would suffer from high propagule pressure. Results revealed a mismatch between areas with high spread potential and those with high propagule pressure. Managers should concentrate their invasion prevention efforts in the former because these are likely to have a greater long‐term influence. Additionally, we predicted future expansion from the current distribution and showed that current scattered populations could merge naturally. Our approach is useful for establishing a management plan before or in the early stages of invasion.